PERSPEKTIF NEW INSTITUTIONAL THEORY ATAS AKUNTABILITAS PAJAK PERGURUAN TINGGI SWASTA - Maryati Maryati (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
Generally, the tax accountability of private universities is still low. This study aims to deeply understand the practice of private university tax accountability. Using a qualitative approach with an interpretive paradigm as a foundation, this research was conducted at XYZ University located in Jakarta. Data collection uses in-depth interviews, participant observation, and documentation. Tax accountability analyzed using the New Institutional Theory approach that developed by Scott (2001) through regulative, normative, and cognitive-cultural values. The results of this study indicate that the tax accountability of XYZ University is still limited. First, based on the regulative pillar, financial managers of university have knowledge and understanding of limited tax regulations so they have not been able to fulfill tax obligations  accordance with tax regulations. Second, based on the normative pillar, the implementation of the tax calculation mechanism does not reflect taxation norms, such as honesty, truth, completeness, and accountability. Third, based on the cognitive-cultural pillar, limited knowledge of tax regulations forms makes the same understanding of financial managers in universities and faculties where the understanding that only Income Tax Article 21 as the university's tax obligation. This limited understanding of the implementation for recurring tax obligations establish its culture of tax accountability.